ANALISIS KANDUNGAN GIZI PRODUK OLAHAN SAYUR LEBUI - Agus Dwi Ananto (Pro Food, 2017)
The high prevalence of malnutrition reflected low food security in West Nusa Tenggara Province. Nutritional, security, sociocultural, and diversification in the processing and utilization of food that has not been optimal to be the cause of it. Lebui [Glycine max (L.) Merril] as a typical vegetable processed product of Lombok island can be one of alternative of food reinforcement. This aims of this research was to determined the water content, ash and anthocyanin processed vegetable products in quantitative and sensory. Evaluation of nutritional content using proximate analysis while receiving aspect using favorite test. The results showed that water, ash, and anthocyanin levels in the samples were 11.366% w / w, 4.116% w / w, 46.757 mg / 100 g respectively while in the processed products had similar results with seeds with the decreasing trend of anthocyanin content . Preferably test shows organoleptically more vegetable variants more desirable from the aspects of taste, texture, and aroma. Processed vegetable products have higher nutritional content and are preferred by consumers so that it can be further developed as a diversificated of food products. Keywords: hedonic test, processed vegetable product, proximate analysis ABSTRAK Angka prevalensi gizi buruk yang tinggi merefleksikan rendahnya ketahanan pangan di Provinsi Nusa Tenggara Barat. Aspek gizi, keamanan, sosiokultural, diversifikasi dalam pengolahan dan pemanfaatan pangan yang belum optimal menjadi faktor penyebab hal tersebut. Lebui [Glycine max (L.) Merril] sebagai produk olahan sayur khas pulau Lombok dapat menjadi salahsatu alternatif penguatan pangan. Penelitian ini bertujuan untuk mengetahui kadar air, abu dan antosianin produk olahan sayur lebui secara kuantitatif dan sensoris. Evaluasi kandungan gizi menggunakan analisa proksimat sementara aspek penerimaan menggunakan uji kesukaan. Hasil penelitian menunjukkan kadar air, abu, dan antosianin pada sampel berturut-turut sebesar 11,366 %b/b, 4,116 %b/b, 46,757 mg/100 g sementara pada produk olahan memiliki hasil yang serupa dengan biji lebui disertai dengan trend penurunan kadar antosianin. Uji kesukaan menunjukkan secara organoleptik varian sayur lebui lebih diminati dari aspek rasa, tekstur, dan aroma. Produk olahan sayur lebui memiliki kandungan gizi yang cukup tinggi dan lebih disukai konsumen sehingga dapat dikembangkan lebih lanjut sebagai diversifikasi produk pangan. Kata kunci:analisa proksimat, produk olahan sayur lebui, uji kesukaan